Ergonomics for needs of elderly and disabled people - Nowak, E. (Array, 1990)
The needs of elderly people with respect to furniture, appliances, and house design differ in many respects from those of younger, healthy people. Frequently, the older person experiences limitations of movement which reduce the effective length of reach. The design of appliances should take into account these limitations to ensure placement of controls within reach of the elderly or disabled user. Chairs and other furniture should be designed to facilitate access and egress for the elderly user who quite often will find chairs that are comfortable for the young user inconvenient and perhaps even hazardous. Improved designs that benefit elderly users may often benefit younger disabled people as well and research leading to such improvements will become increasingly important as the numbers of elderly people increase